Gaudí 2002 : Una gran fiesta hemenéutica - García, Marisa (2002)
Acerca de las exposiciones en Barcelona que celebran el 150 aniversario.
Keywords: GAUDI, ANTONI; ESPAÑA; BARCELONA; EXPOSICIONES; CRITICA